2020
DOI: 10.1063/5.0020818
|View full text |Cite
|
Sign up to set email alerts
|

Near-wall effect on flow around an elliptic cylinder translating above a plane wall

Abstract: In this work, the flow over an elliptic cylinder near a moving wall is investigated for Reynolds numbers less than 150. Here, the ratio between the gap (i.e., the distance between the cylinder and the wall) and the length of the semi-major axis of the elliptic cylinder varies from 0.1 to 5. This ratio is hereafter denoted as the gap ratio. The resulting Kármán vortex street, the two-layered wake, and the secondary vortex street have been investigated and visualized. Numerical simulations show that for the stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…In the present work, the near-wall effect leads to the two-layered wake moving upstream, thus suppressing the near-wake instability. This upstream movement of the two-layered wake caused by the near-wall effect was previously demonstrated by Zhu et al 20 for two-dimensional flow past an elliptic cylinder near a moving wall.…”
Section: Near-wake Two-dimensional Flow Regimesupporting
confidence: 72%
See 3 more Smart Citations
“…In the present work, the near-wall effect leads to the two-layered wake moving upstream, thus suppressing the near-wake instability. This upstream movement of the two-layered wake caused by the near-wall effect was previously demonstrated by Zhu et al 20 for two-dimensional flow past an elliptic cylinder near a moving wall.…”
Section: Near-wake Two-dimensional Flow Regimesupporting
confidence: 72%
“…for wake pattern D identified by Zhu et al 20 for two-dimensional flow. Thus, this flow, depicted in figure 18, is denoted as the three-dimensional wake pattern D. For G/D = 0.2, the following wake transitions are found: For Re ≤ 120, the flow is twodimensional and steady without vortex shedding.…”
Section: Chaotic Flow Regimementioning
confidence: 81%
See 2 more Smart Citations
“…Moreover, this flow configuration can be used to investigate the effect of gap ratio on the transition from the Kármán vortex street to the two-layered wake and the transition from the two-layered wake to the secondary vortex street which do not occur for a circular cylinder translating above a plane wall at the same Re range 18 . Four wake patterns have been classified by Zhu et al 23 for flow around an elliptic cylinder with AR = 0.4 and AOA = 0 o near a moving wall for Re ≤ 150 with G/D ∈ [0.1, 5]; i) at relatively large G/D, the flow, which is denoted as wake pattern A, contains the Kármán vortex street, the two-layered wake and the secondary vortex street; ii) a decrease of G/D suppresses the secondary vortex street, forming the wake pattern B; iii) a further decrease in G/D leads to the break-down of the Kármán vortex, resulting in a pair-wise vortex shedding (denoted wake pattern C) or iv) forming a quasi-steady near-wake region (with time-independent lift and drag coefficients) and a pair-wise vortex shedding farther downstream (denoted wake pattern D). They also found that the critical Re for the transition between the different wake patterns increases as G/D increases.…”
Section: Introductionmentioning
confidence: 99%